Effectiveness and Reflection: Short Video Marketing Explodes the Market of Domestic Literary Films– A Case Study of Return to Dust - Wei, Qu; Haiyan, Chen (Published by Confucius Institute UNS, 2000)
The audience spontaneously acted as